2008
DOI: 10.1016/j.addbeh.2008.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Computer-based interventions for college drinking: A qualitative review

Abstract: E-Interventions, or electronically based interventions, have become increasingly popular in recent years. College alcohol use has been one area in which such interventions have been implemented and evaluated. The purpose of this paper is to review the seventeen randomized controlled trials that have been published as of August 2007. These studies compared the effectiveness of e-interventions with other commonly used techniques, reading materials, and assessment-only control conditions. Overall, findings provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 34 publications
3
116
1
1
Order By: Relevance
“…The results are consistent with previous studies, in which feedback based computerized intervention is more effective for participants with specific individual characteristics at baseline, such as hazardous drinking students (Canale et al, 2015;Palfai et al, 2011), since students who are heavier drinkers may experience feedback as more relevant and salient than those who not drink so heavily (Elliott, Carey, & Bolles, 2008). It is interesting to observe that baseline FGs receiving intervention showed 14 more realistic attitudes toward the profitability of gambling (even if not significant), while baseline FGs receiving only the PF about estimated risk-status and tips for safer gambling, without additional training (interactive activities), showed significantly less realistic attitudes toward the profitability of gambling post-intervention.…”
Section: Discussionsupporting
confidence: 91%
“…The results are consistent with previous studies, in which feedback based computerized intervention is more effective for participants with specific individual characteristics at baseline, such as hazardous drinking students (Canale et al, 2015;Palfai et al, 2011), since students who are heavier drinkers may experience feedback as more relevant and salient than those who not drink so heavily (Elliott, Carey, & Bolles, 2008). It is interesting to observe that baseline FGs receiving intervention showed 14 more realistic attitudes toward the profitability of gambling (even if not significant), while baseline FGs receiving only the PF about estimated risk-status and tips for safer gambling, without additional training (interactive activities), showed significantly less realistic attitudes toward the profitability of gambling post-intervention.…”
Section: Discussionsupporting
confidence: 91%
“…The search strategies are shown in Appendix Table 2 (available at www.annals.org). We reviewed bibliographies of included trials and applicable systematic reviews for missed publications (14)(15)(21)(22)(23)(24)(25). To assess for publication bias, we searched ClinicalTrials.gov for trials that met our eligibility criteria (26) and found 2 trials that were completed at least 1 year before our literature search but were unpublished.…”
Section: Data Sources and Searchesmentioning
confidence: 99%
“…Several literature reviews have summarized the evidence on alcohol interventions' effectiveness for college students (e.g., Branscum & Sharma, 2010;Carey et al, 2007Carey et al, , 2009Cronce & Larimer, 2011;Elliott et al, 2008;Fachini et al, 2012;Labbe & Maisto, 2011;Larimer & Cronce, 2002Moreira et al, 2009). In one of the most comprehensive reviews to date, Carey and colleagues (2007) meta-analyzed findings from 62 randomized controlled trials, many of which involved single-session brief interventions.…”
Section: Effectiveness Of Brief Alcohol Interventionsmentioning
confidence: 99%